Marketing Strategy and Customer Value of Astuti Wedding Gallery Using SWOT, QSPM, and VPC - Mutmainna (Program Studi Bisnis Digital - Fakultas Ekonomi dan Bisnis Islam, 2025)
This research examines the culture-based service development strategy at Astuti Wedding Gallery (AWG), a Javanese traditional wedding service provider in Samarinda. This study is based on the increasing interest of the younger generation towards the concept of traditional marriage combined with a modern touch, Theoretically, the study uses SWOT analysis to assess the company’s internal and external positions, as well as Value Proposition Canvas (VPC) to understand customer needs and the appropriateness of the value provided. The method used is a qualitative approach through interview, observation, and triangulation to ensure the validity of the data. The research result show that the main advantage of AWG comes from the uniqueness of Javanese culture, good interpersonal relationship with clients, and the flexibility of service packages. Weaknesses are found in limited manpower, digital promotion that is not optimal, and operational system that is not organized. Opportunities are created through traditional marriage trend and the expansion of digital marketing, while threats come from industry competition and changing economic conditions. Based on SWOT, VPC, and QSPM analysis, the most appropriate strategy is market development through the use of digital media and cooperation with local vendors. Overall the integration of cultural values with modern innovation is the basis for increasing AWG’s competitiveness.